Strawberry Farm Information Management System - Pandian, Amirta Varsheni; Nureize Arbaiy, (Applied Information Technology And Computer Science, 2025)
Modern agriculture is increasingly reliant on information management systems to optimize productivity. Implementation of Farm Information Management Systems (FMIS) has become quite the trend in farming, in this context. Healthy Strawberry Farm, traditionally run in the hills of Cameron Highlands for over 50 years, has been facing difficulties when it comes to accessing real-time information regarding farm management. Data can be highly unreliable especially when they are recorded manually and crop and labor management is quite a tedious task at present. Therefore, a strawberry farm information management system has been developed to assist the management. The system aims to facilitate the internal operation of the farm while making it not only highly accessible to users but also to provide reliable data. PHP, Xampp, and MySQL are used in system development, and agile techniques for iterative development and change adaptation are applied. The web-based strawberry farm information management system is expected to fulfill the requirements of the farm manager and owner, designed to enhance the productivity of staff, the quality of crop and the overall management of the farm. The system will further help the farm to stand out among other traditionally run farms, giving them the vantage to explore the advancement in technology as the sytem promotes data-driven decision making for better productivity.